The impact of performance measures on strengthening the resilience of supply chains: a review - Matsuyama, Suzana; Chaves, Gisele de Lorena Diniz (Brazilian Journal of Production Engineering, 2024)
Supply chain measures are essential for assessing a company’s performance. This study examines the interaction between supply chain performance measures and the elements that strengthen resilience. Through the analysis of a portfolio of 22 articles, 18 elements that contribute to resilience and a set of 75 metrics related to the supply chain were identified. The study established connections between these measures and the key elements of resilience, also considering logistical and multifunctional variables. In addition, it was possible to identify in the study how certain measures mentioned directly impact other measures related to the supply chain. The study summarizes relevant information on measures that can be used to increase resilience in supply chains, serving as a basis for research content in both academic and managerial contexts